2012
DOI: 10.1088/0022-3727/45/49/494002
|View full text |Cite
|
Sign up to set email alerts
|

Atomic structure analysis of stacking faults and misfit dislocations at 3C-SiC/Si(0 0 1) interfaces by aberration-corrected transmission electron microscopy

Abstract: The interfacial atomic structures of 3C-SiC/Si(0 0 1) and the dislocation core structures related to generation and annihilation of stacking faults are clarified by aberration-corrected transmission electron microscopy combined with image processing called the ‘image subtraction and improved deconvolution (ISD)’ method. Details of the intrinsic interfacial structure are explained in terms of a two-dimensional network of partial edge dislocations and Lomer dislocations. Around the junction of the interface and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…10b) are in agreement with the CSS type. The results of this study, combining with the view given in Wen et al (2009), indicate that both S1a and CSS type Lomer dislocations should be stable and frequently existed at the 3C-SiC/Si (0 0 1) interface, if not discussing about the core structure of Lomer dislocation proposed recently (Inamoto et al, 2011;Yamasaki et al, 2012).…”
Section: Atomic Configuration Of Interfacial Misfit Dislocationssupporting
confidence: 56%
“…10b) are in agreement with the CSS type. The results of this study, combining with the view given in Wen et al (2009), indicate that both S1a and CSS type Lomer dislocations should be stable and frequently existed at the 3C-SiC/Si (0 0 1) interface, if not discussing about the core structure of Lomer dislocation proposed recently (Inamoto et al, 2011;Yamasaki et al, 2012).…”
Section: Atomic Configuration Of Interfacial Misfit Dislocationssupporting
confidence: 56%
“…Stacking faults (SFs) are the most important ones dominating over the entire 3C-SiC layer thickness. In literature, three types of SFs are observed depending on the number of atomic planes with the wrong orientation: SFs can have 1, 2, or 3 errors in the stacking sequence and they are called intrinsic (or SF<1>), extrinsic (or SF<2>), or conservative (or SF<3>) [ 40 , 55 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…where a is the lattice constant. 16 It is worth noting that several authors have also observed that a high density of SFs exist in regions of the material where grain boundary are found, 9 implying that a relationship between them exists. While it is known that an IDB can terminate a SF, 3 the details of the relationship between IDBs and SFs have not been studied for SiC, and even more interestingly the generation of SFs from IDB has never been reported in 3C-SiC.…”
Section: ■ Introductionmentioning
confidence: 97%